2010
DOI: 10.1111/j.1752-8062.2010.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Significant Downregulation of Platelet Gene Expression in Metastatic Lung Cancer

Abstract: IntroductionPlatelets arise as cytoplasmic fragments from megakaryocytes in the bone marrow. Thus they are anucleate, but retain megakaryocyte-derived cytoplasmic pre-mRNA, at least some of which is spliced into mRNA and translated into protein in response to external stimulation through surface receptor activation and outside-in signaling. [1][2][3] Previously unrecognized synthetic capabilities of platelets have recently emerged and the profi le of proteins released by activated platelets (the "secretome") h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 28 publications
2
100
0
5
Order By: Relevance
“…Body mass index and circulating levels of C‐reactive protein and interleukin‐6 are also associated with changes in platelet gene expression , and there are many other published lines of evidence consistent with the supposition that human diseases are associated with changes in the genetic code of platelets . While an in‐depth discussion of these established and emerging findings is beyond the scope of the current brief review, the reader is encouraged to keep an eye on this rapidly evolving area of investigation.…”
Section: Megakaryocyte Investment Of the Genetic Code Into Plateletsmentioning
confidence: 81%
See 1 more Smart Citation
“…Body mass index and circulating levels of C‐reactive protein and interleukin‐6 are also associated with changes in platelet gene expression , and there are many other published lines of evidence consistent with the supposition that human diseases are associated with changes in the genetic code of platelets . While an in‐depth discussion of these established and emerging findings is beyond the scope of the current brief review, the reader is encouraged to keep an eye on this rapidly evolving area of investigation.…”
Section: Megakaryocyte Investment Of the Genetic Code Into Plateletsmentioning
confidence: 81%
“…These findings also support the hypothesis that in SLE patients, circulating IFNa production by plasmacytoid dendritic cells may alter the genetic code of megakaryocytes within the bone marrow niche, leading to the production of platelets enriched for IFN-regulated proteins. Body mass index and circulating levels of C-reactive protein and interleukin-6 are also associated with changes in platelet gene expression [40,41], and there are many other published lines of evidence consistent with the supposition that human diseases are associated with changes in the genetic code of platelets [30,[42][43][44][45]. While an indepth discussion of these established and emerging findings is beyond the scope of the current brief review, the reader is encouraged to keep an eye on this rapidly evolving area of investigation.…”
Section: Megakaryocyte Investment Of the Genetic Code Into Plateletsmentioning
confidence: 82%
“…26 It was recently shown that megakaryocytes selectively transport mRNAs into platelets, allowing only a subset of RNAs to be transferred into platelets, 27 and Calverly et al identified a subset of megakaryocyte/platelet-derived mRNAs that are differentially expressed in lung cancer metastasis. 28 However, any role of tumorderived RNA in platelet biology and cancer remains to be investigated, and it remains unclear to what extent the transferred tumor-derived RNA can be functionally translated into proteins, thereby manipulating platelet function, as previously shown to occur in endothelial cells after uptake of tumor-derived microvesicles. 12 A recent study demonstrated miR-28 to be deregulated in platelets of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified diagnostic platelet RNA signatures for cardiovascular abnormalities , inflammatory conditions , sickle cell disease , essential thrombocytosis , and cancer . In 2010, Calverley et al .…”
Section: Alterations Of Platelet Rna In Patients With Cancermentioning
confidence: 99%
“…In 2010, Calverley et al . used micro‐array analysis to profile the platelet mRNA of seven healthy individuals and five patients with metastatic lung cancer . The platelet samples of the patients with lung cancer were collected prior to any treatment, and 200 altered RNAs were discovered between the healthy individuals and the patients with lung cancer, of which 197 genes (99%) were decreased in platelets of patients with lung cancer.…”
Section: Alterations Of Platelet Rna In Patients With Cancermentioning
confidence: 99%